Pentingnya Penerapan Pemikiran Nurcholish Madjid Mengenai Etika Politik di Indonesia: Bentuk-Bentuk Etika Politik Nurcholish Madjid dan Urgensi Penerapan Etika Politik Pemikiran Nurcholish Madjid di Indonesia - Yusnadia Achda Saputri; Muhammad Nur Hidayat; Kurniati Kurniati (Fakultas Ilmu Sosial dan Ilmu Politik - Universitas Garut, 2024)
Political ethics that are lacking in both government and society often create an environment where Corruption, Collusion, and Nepotism (CCN) can thrive unchecked. These CCN practices not only cause economic harm but also threaten social and political justice within the community. Injustice in wealth distribution and opportunity is another frequent consequence of this lack of political ethics. Furthermore, the Pancasila ideology, as the foundation of the Indonesian state, is often obscured in everyday political practice. This obscuration can hinder the democratization process and the achievement of social justice envisioned by the nation's founders. Nurcholish Madjid, an Indonesian Muslim intellectual, offers a pertinent perspective on improving political ethics. According to Madjid, good political ethics should be based on the principle of equitable justice for all citizens and promote inclusive and participatory democracy. Madjid also emphasizes the importance of transparency in the political process, where the public has broad access to information and government decisions. Referring to Madjid's thoughts, efforts to enhance political ethics in Indonesia can be achieved by emphasizing values of justice, democracy, and transparency. This not only reduces CCN practices and injustice but also creates greater space for the recognition and implementation of Pancasila values in Indonesian political and social life as a whole. Nurcholish's political thoughts, if applied in national life, especially in the current context, are highly relevant because Indonesia still needs a better and more just political system and order. It is time for Indonesia to reform and reshape not only a more democratic and socially just political framework but also to realize political ethics as described above, which tend to be neglected.